Hubungan antara Motivasi dengan Komitmen Organisasi di Sekolah Menengah Atas Negeri Wilayah I Kota Administrasi Jakarta Timur - Alfianto, Cahyo; Karnati, Neti; Armeliza, Diah (Program Studi Manajemen Pendidikan, 2016)
This study aims to determine whether there is a relationship between motivation with Organizational Commitment at Senior High School Region 1 East Jakarta Administration. The research approach was quantitative research. The research method used was survey data. With the analysis of correlational studies. The population in this study were all teachers Senior High School in Region I East Jakarta Administration. The research sample using simple random sampling technique. Total sample study as many as 91 people. Data collection motivation variable (X) and organizational commitment variable (Y) using a questionnaire. The results of the study there is a relationship between motivation and commitment to the organization, this means that the higher the motivation, the higher organizational commitment of teachers at the Senior High School Region I East Jakarta Administration.